Passengers’ Satisfaction towards Service Quality with Public Transportation in Kathmandu Valley - Manandhar, Raju Bhai (International Research Journal of MMC, 2023)
The operation of public transportation is a public service. Nepal's only cooperative public transportation system is Sajha Yatayat. Additionally, many public transportation options are operated by private companies. Kathmandu is the capital of Nepal; hence the population and public transportation are under significant strain. Therefore, this location was chosen for the research on passengers' satisfaction with the service quality of public transportation. The survey issued 80 questionnaires to riders of public transportation. 52 surveys were returned. Forty of the samples were valid for analysis. 26 passengers (65%) said that evening and nighttime access to public transportation was extremely limited. In addition, 16 (40%) of respondents felt uneasy riding in public transportation. Similarly, 27 (67.5%) respondents noted poor hygiene, and 22 (55%), dangerous public transportation. However, the majority of passengers are dissatisfied with the accessibility, comfort, cleanliness, and safety of public transportation. Only the transportation fare provides satisfaction to passengers. In order to increase passenger happiness, the relevant authority should be accountable for enhancing the service quality of public transportation.